Effects of soil degradation on infiltration rates in grazed semiarid rangelands of northeastern Patagonia, Argentina - Chartier, Marcelo Pablo (2011)
In grazed semiarid ecosystems, considerable spatial variability in soil infiltration exists as a result of vegetation and soil patchiness. Despite widespread recognition that important interactions and feedbacks occur between vegetation, runoff and erosion, currently there is only limited quantitative information on the control mechanisms that lead to differences in infiltration from different vegetation types. In this paper, we determine (i) the relationship between vegetation and soil surface characteristics and (ii) the soil infiltration rate by using rainfall simulations on runoff plots (0.60 x 1.67 m) in three plant communities of northeastern Patagonia: grass (GS), degraded grass with scattered shrubs (DGS), and degraded shrub steppes (DSS). Our results clearly indicate that vegetation and soil infiltration are closely coupled. Total infiltration was significantly higher in the GS (69.6 mm) compared with the DGS and DSS (42.9 and 28.5 mm, respectively). In the GS, soil infiltration rate declined more slowly than the others communities, reaching a terminal infiltration rate significantly greater (57.7 mm) than those of DGS and DSS (25.7 and 12.9 mm, respectively). The high rate of water losses via overland-flow may limit the possibilities for grass seedling emergence and establishment and favor the persistent dominance of shrubs.